Balancing strength and porosity: A critical evaluation of cement substitution with metakaolin in porous concrete - Rahmadillah, Auliya; Adhitya, Bimo Brata; Sari, Fitria Putri Lintang (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
Rapid urbanization has led to increased impervious surfaces, exacerbating stormwater runoff and urban flooding. As a response, pervious concrete has emerged as an innovative solution in sustainable infrastructure due to its high porosity, enabling water infiltration and flood mitigation. This study evaluates the impact of varying percentages of metakaolin as a partial cement substitute on the mechanical properties, permeability, and porosity of pervious concrete. Metakaolin, as a reactive pozzolanic material, is expected to enhance mechanical strength while maintaining the concrete’s drainage function. Five mix variations with 10%, 12.5%, 15%, 17.5%, and 20% metakaolin as a partial cement substitute were tested at concrete ages of 7 and 28 days. The results show that the optimal composition was achieved with a 15% metakaolin substitution, yielding 13.17 MPa compressive strength, 3.87 MPa splitting tensile strength, 0.469 cm/s permeability, and 24.34% porosity at 28 days. The addition of metakaolin in moderate amounts improves density and structural strength, but higher proportions significantly reduce permeability. These findings highlight the importance of achieving a balance between mechanical performance and hydraulic function in metakaolin-based pervious concrete design.